International remote collaboration enabled inaugural endoscopic sleeve gastroplasty in Japan. Issue 1 (25th August 2021) - Dobashi, Akira; Uno, Kohei; Matsui, Hiroaki; Furuhashi, Hiroto; Futakuchi, Toshiki; Kamba, Shunsuke; Ono, Shingo; Tamai, Naoto; Watanabe, Atsushi; Gostout, Christopher J.; Sumiyama, Kazuki
Abstract: Obesity causes multiple conditions such as type 2 diabetes, cardiovascular disease, and so on, and an intervention is needed for controlling weight and improving metabolic syndrome. However, the effectiveness of lifestyle interventions and pharmacotherapy are restrictive for losing weight. Endoscopic sleeve gastroplasty (ESG) was developed as a new therapy, picking the best of both medication and surgery, less invasive and more effective. Recently, ESG is gradually spreading in Western countries, but there is Case report doesn't need conclusion/result for Japanese patients. We herein reported the first clinical case of ESG in Japan. Given the situation of the pandemic of COVID‐19, we could not invite a proctor from Western countries and receive the instruction of the device setting and maneuver face to face. Thus, we conducted the training for device setting, maneuver, and operation under a web‐based international remote collaboration. Eventually, we completed ESG without an adverse event. We could prove this web‐based proctor system was useful through the introduction of ESG in Japan. The international remote collaboration could become a new normal even in the endoscopy field post‐COVID‐19 era.